(untitled) (GnosisWisdom, 2024)
Antonio José Brack Egg was a Peruvian educator, naturalist, biologist, photographer and environmental journalist, expert in the environment and sustainable development. His work from 1973 to the present had a significant impact on the country and different regions of Latin America. From his pedagogical studies in Lima to his appointment as Minister of the Environment, he has worked on a wide range of projects, from the management of nature reserves to environmental education. His influence extends through publications, environmental development plans, educational television programs, and recognition for his dedication to public service and environmental conservation.